1990
DOI: 10.1172/jci114495
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between myocardial metabolites and contractile abnormalities during graded regional ischemia. Phosphorus-31 nuclear magnetic resonance studies of porcine myocardium in vivo.

Abstract: The mechanisms responsible for changes in myocardial contractility during regional ischemia are unknown. Since changes in high-energy phosphates during ischemia are sensitive to reductions in myocardial blood flow, it was hypothesized that myocardial function under steady-state conditions of graded regional ischemia is closely related to changes in myocardial high-energy phosphates. Therefore, phosphorus-31 nuclear magnetic resonance spectroscopy was employed in an in vivo porcine model of graded coronary sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Our data agree with the work of Clark [II] and Schafer et al [12] who have demonstrated in animal models of acute ischemia that hydrogen ion concentration was the slowest changing variable, lagging far behind functional changes. However, acidosis affects every step in the excitation-contraction coupling pathway including both the delivery of calcium to the myofilaments and the response of the myofilaments to calcium.…”
Section: Com M Entsupporting
confidence: 93%
“…Our data agree with the work of Clark [II] and Schafer et al [12] who have demonstrated in animal models of acute ischemia that hydrogen ion concentration was the slowest changing variable, lagging far behind functional changes. However, acidosis affects every step in the excitation-contraction coupling pathway including both the delivery of calcium to the myofilaments and the response of the myofilaments to calcium.…”
Section: Com M Entsupporting
confidence: 93%
“…by 30% for a 60% reduction in regional flow in pig heart [27]. However, even if regional blood flow in pig myocardium is reduced by 90%, leading to a reduction of PCr by some 80%, the ATP content is still not reduced and apparently is still buffered well by PCr [27]. This is in agreement with theoretical considerations of the creatine kinase and adenylate kinase high-energy phosphate buffering system which show that ATP is virtually constant until PCr drops below 10% of its normal level.…”
Section: Limitations Of Methodsmentioning
confidence: 96%
“…by 30% for a 60% reduction in regional flow in pig heart [27]. However, even if regional blood flow in pig myocardium is reduced by 90%, leading to a reduction of PCr by some 80%, the ATP content is still not reduced and apparently is still buffered well by PCr [27].…”
Section: Limitations Of Methodsmentioning
confidence: 99%
“…It has previously been shown that Cre levels, belonging to the myocardial energy index, are related to myocardial functional performance under ischemic conditions in animal hearts in vivo (37). In 31 P-MRS, PCr and ATP represent the level of myocardial energy.…”
Section: Discussionmentioning
confidence: 99%